A Convenient Preparation of Bis(4‐methoxyphenyl)methanethiol and Its Application in the Synthesis of Biotin Thioacid. Issue 6 (11th March 2014) - Chou, Tzyy‐Chao; Hsu, Yu‐Ling; Lo, Lee‐Chiang
Abstract We have established a facile protocol for the preparation of bis(4‐methoxyphenyl)methanethiol (4). Thiol 4 was used to prepare biotin thioester 7 which was later subjected to acidolysis to afford biotin thioacid (1b) in high yield. Compound 1b represents a new biotinylating reagent worth exploring and its spectral data was reported for the first time.